Pengelolaan Cashflow Penjualan UMKM Artie Tasty dengan Pelatihan Pembuatan Laporan Keuangan Sederhana - Indrayani, Lioni; Permadi, Wisjnumurti Bambang; Arini , Dewi Ulfah (Yayasan Cita Cendikiawan Al Kharizmi, 2022)
Since the entry of the Covid-19 virus in Indonesia people's mobility has been restricted. Activities in the world of education and the economy are no longer face-to-face but are changing online. This situation made many businesses and entertainment venues closed and the direct result was layoffs for employees. This situation has spurred Micro, Small and Medium Enterprises to proliferate during the pandemic. This situation made the Lecturer Team from the Accounting Study Program want to create a Community Service Activity by providing income statement training to Artie Tasty SMEs who are members of the Pamulang Estate SMEs. Artie Tasty is an MSME that sells snacks, the main products marketed are self-produced risoles, rogut and potato donuts. With this community service activity from the Lecturer Team of the Pamulang University Accounting Study Program, it is hoped that it can be a solution for Artie Tasty in organizing their profit.